Plexin B3 guides axons to cross the midline in vivo - Liu, Zhi-Zhi; Liu, Ling-Yan; Zhu, Lou-Yin; Zhu, Jian; Luo, Jia-Yu; Wang, Ye-Fan; Xu, Hong A. (Frontiers in Cellular Neuroscience, 2024)
During the development of neural circuits, axons are guided by a variety of molecular cues to navigate through the brain and establish precise connections with correct partners at the right time and place. Many axon guidance cues have been identified and they play pleiotropic roles in not only axon guidance but also axon fasciculation, axon pruning and synaptogenesis as well as cell migration, angiogenesis and bone formation. In search of receptors for Sema3E in axon guidance, we unexpectedly found that Plexin B3 is highly expressed in retinal ganglion cells of zebrafish embryos when retinal axons are crossing the midline to form the chiasm. Plexin B3 has been characterized to be related to neurodevelopmental disorders. However, the investigation of its pathological mechanisms is hampered by the lack of appropriate animal model. We provide evidence that Plexin B3 is critical for axon guidance in vivo. Plexin B3 might function as a receptor for Sema3E while Neuropilin 1 could be a co-receptor. The intracellular domain of Plexin B3 is required for Semaphorin signaling transduction.Our data suggest that zebrafish could be an ideal animal model for investigating the role and mechanisms of Sema3E and Plexin B3 in vivo.